Effective Leadership Achieves Organizational Goals in Indonesia: Kepemimpinan yang Efektif Mencapai Tujuan Organisasi di Indonesia - Shobakh, Nur Izzatus; Mursyidah, Lailul (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the crucial role of leadership in achieving organizational goals at the Food and Agriculture Office of Sidoarjo Regency. Using a qualitative descriptive method, data were collected through observation, interviews, and documentation, and analyzed using the Interactive Data Model by Miles, Huberman, and Saldana. Findings show that effective leadership—particularly directive, participative, and supportive styles—significantly contributes to achieving organizational goals by providing direction, guidance, and support, involving subordinates in decision-making, and recognizing their performance. This research highlights the importance of appropriate leadership practices in enhancing organizational performance. Highlight: Leadership styles boost organizational performance: directive, participative, supportive. Data collected through observation, interviews, documentation; analyzed interactively. Leaders guide, support, involve in decisions, recognize performance. Keywoard: Leadership, Organizational Goals, Qualitative Research, Sidoarjo Regency, Food and Agriculture Office